Cyclization/Hydrosilylation of Functionalized 1,6-Diynes Catalyzed by Cationic Platinum Complexes Containing Bidentate Nitrogen Ligands - Wang, Xiang; Chakrapani, Harinath; Madine, James W; Keyerleber, Michele A; Widenhoefer, Ross A (Journal of organic chemistry, 2002)
A 1:1 mixture of the platinum dimethyl diimine complex [PhNC(Me)C(Me)NPh]PtMe2 (4a) and B(C6F5)3 catalyzed the cyclization/hydrosilylation of dimethyl dipropargylmalonate (1) and HSiEt3 to form 1,1-dicarbomethoxy-3-methylene-4-(triethylsilylmethylene)cyclopentane (3) in 82% isolated yield with 26:1 Z:E selectivity. Platinum-catalyzed diyne cyclization/hydrosilylation tolerated a range of functional groups including esters, sulfones, acetals, silyl ethers, amides, and hindered ketones. Diynes that possessed propargylic substitution underwent facile cyclization/hydrosilylation to form silylated 1,2-dialkylidene cyclopentanes as mixtures of regioisomers. Diynes that possessed an electron-deficient internal alkyne underwent cyclization/hydrosilylation in moderate yield to form products resulting from silyl transfer to the less substituted alkyne. The silylated 1,2-dialkylidenecyclopentanes formed via diyne cyclization/hydrosilylation underwent a range of transformations including protodesilylation, Z/E isomerization, and [4 + 2] cycloaddition with dieneophiles.